2019
DOI: 10.7554/elife.48686
|View full text |Cite
|
Sign up to set email alerts
|

TRAIP drives replisome disassembly and mitotic DNA repair synthesis at sites of incomplete DNA replication

Abstract: The faithful segregation of eukaryotic chromosomes in mitosis requires that the genome be duplicated completely prior to anaphase. However, cells with large genomes sometimes fail to complete replication during interphase and instead enter mitosis with regions of incompletely replicated DNA. These regions are processed in early mitosis via a process known as mitotic DNA repair synthesis (MiDAS), but little is known about how cells switch from conventional DNA replication to MiDAS. Using the early embryo of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 31 publications
1
88
0
Order By: Relevance
“…However, other studies conclude that CMG is not involved in BIR (Dilley et al, 2016;Natsume et al, 2017;Sonneville et al, 2019;Wilson et al, 2013). To determine whether CMG could function in replication restart, tracking its fate during replication stress in a physiological setting is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies conclude that CMG is not involved in BIR (Dilley et al, 2016;Natsume et al, 2017;Sonneville et al, 2019;Wilson et al, 2013). To determine whether CMG could function in replication restart, tracking its fate during replication stress in a physiological setting is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…CFSs require FANCD2 for efficient replication (Madireddy et al, 2016) and have been identified as regions where active DNA synthesis is apparent on mitotic chromosomes in a process dependent on POLD3 and the Mus81 nuclease (Minocherhomji et al, 2015). The exact steps involved in triggering synthesis remain unknown but it also requires the TRAIP ubiquitin ligase (Sonneville et al, 2019) and may be active at regions of the genome that are incompletely condensed in mitosis. Recently, condensation defects have also been shown to underlie HR-deficiency mediated mitotic lesions, and if not resolved lead to DNA damage and chromosomal instability (Chan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These works have found that the RING E3 ubiquitin ligase TRAIP is an important regulator of the processing of incomplete DNA replication during mitosis in metazoan. Thus, TRAIP drives replisome disassembly at those under-replicated CFS loci, thereby allowing access to replication fork for the specific factors in charge for mitotic DNA synthesis [194]. In addition, the activity of TRAIP during mitosis seems to be regulated by Cdk1-Cyclin B1 complexes [56,194,195], which control the accurate timing of mitosis and also regulate the switch from conventional DNA replication to MiDAS machineries (Table 1).…”
Section: Mitotic Dna Synthesismentioning
confidence: 99%
“…Thus, FANCD2 is involved in the repair of interstrand crosslinks facilitating CFS replication completion and stability before mitosis [134], extending its function beyond the S-phase, and participating in unscheduled DNA synthesis in late G2 to early mitosis, as already mentioned. Although the precise function of FANCD2 in MiDAS is currently poorly understood, it has been shown that the depletion of TRAIP impairs FANCD2 foci formation in mitosis, as well as mitotic DNA replication [194]. Future studies will be needed to determine if this observation is just a correlation or if FANCD2 indeed plays an active role in MiDAS.…”
Section: Mitotic Dna Synthesismentioning
confidence: 99%